Around-knee osteotomy conversion for failed high tibial osteotomy: Re-correction high tibial osteotomy and additional distal femoral osteotomy may enable return to sporting activities - Ryuichi Nakamura; Masaki Takahashi; Tomoyuki Shimakawa; Kazunari Kuroda; Yasuo Katsuki; Akira Okano (Elsevier, 2022)
High tibial osteotomy (HTO) for knee osteoarthritis achieves excellent short- and long-term results. However, failure of HTO due to undercorrection or correction loss may necessitate conversion surgery. For patients with HTO failure who desire a return to sporting activities (RTS), non-prosthetic joint-preserving solutions such as conversion to around-knee osteotomies (AKO-conversion) may be more appropriate than total knee arthroplasty. The present study aimed to introduce potential non-prosthetic joint-preserving solutions for failed HTO and investigate the postoperative RTS. Among the patients who received non-prosthetic solutions for failed HTO from 2015 to 2020, this case series included those who were eager to RTS, were participating in a sporting activity with a Tegner activity scale score of ≥5 immediately before being affected by knee osteoarthritis, and had at least 2 years of follow-up. Deformity analysis for the preoperative planning of the AKO-conversion was based on the mechanical lateral distal femoral angle, joint line convergence angle, and mechanical medial proximal tibial angle. Four patients met the study inclusion criteria: two patients who underwent re-correction HTO and two who received additional distal femoral osteotomy (DFO). The average ages at primary HTO and AKO-conversion were 69.5 ± 11.8 years and 71.5 ± 10.9 years, respectively. The hip-knee-ankle angle was corrected from −2.8 ± 1.5° before conversion surgery to 3.3 ± 1.5° at 2 years after AKO-conversion. All four patients finally achieved a better sporting performance after AKO-conversion than preoperatively, and the Tegner activity scale score was improved from 2.5 ± 1.0 before AKO-conversion to 5.8 ± 0.5 at the 2-year follow-up. The duration between AKO-conversion and full RTS was 11.8 ± 6.7 months. In conclusion, two patients who underwent re-correction HTO and two who underwent additional DFO for undercorrection or correction loss after primary HTO achieved highly satisfactory clinical results, including RTS. The present findings suggest that non-prosthetic joint-preserving solutions using AKO for failed HTO should be considered as options to enable RTS.